2020
DOI: 10.1007/s13300-020-00935-6
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the National Guidelines for Follow-Up Protocol in Subjects with Type 2 Diabetes Mellitus in Greece: The GLANCE Study

Abstract: Introduction: Physician adherence, or lack therefore, to diabetes care and follow-up guidelines may be linked to the rates of achieving suboptimal glycaemic, blood pressure and lipid targets in people with type 2 diabetes mellitus (T2DM). In this cross-sectional study we evaluated physician adherence to the patient follow-up protocol (PFP) of the 2017 Hellenic Diabetes Association (HDA) guidelines and also assessed glycated haemoglobin (HbA 1c), blood pressure and lipid control achievement rates in the routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…(b) In a retrospective cross-sectional study, HbA1c <7% was achieved by 42% of the patients [ 29 ]. (c) In a cross-sectional study conducted in 15 hospital-based outpatient clinics and 38 private practices located across Greece, HbA1c target was achieved by 82.1% of the subjects [ 30 ]. (d) A cross-sectional disease registry of current T2DM management, representing the majority of Diabetes Centers or Diabetes Outpatients Clinics, showed that the mean (±SD) HbA1c of the total population was 7.1 ±1.2% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) In a retrospective cross-sectional study, HbA1c <7% was achieved by 42% of the patients [ 29 ]. (c) In a cross-sectional study conducted in 15 hospital-based outpatient clinics and 38 private practices located across Greece, HbA1c target was achieved by 82.1% of the subjects [ 30 ]. (d) A cross-sectional disease registry of current T2DM management, representing the majority of Diabetes Centers or Diabetes Outpatients Clinics, showed that the mean (±SD) HbA1c of the total population was 7.1 ±1.2% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey conducted in the United States, 35% of patients with hypertension had their BP under control [ 62 ]. In the routine care setting in Greece, BP target was achieved by 42.6% of subjects with T2DM [ 30 ]. In our study, blockade of the rennin-angiotensin-aldosterone system with either an angiotensin-converting enzyme inhibitor (ACE-1) or an angiotensin II receptor blocker (ARB) were the most frequent antihypertensive agents in all stages of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] However, those individuals with prediabetes who successfully lose weight, maintain a physical activity program and improve their lifestyle can be expected to benefit from decreased conversion to Diabetes. [17]…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Most of the general practitioners reported that some patients were refused to change or improve their lifestyles through weight loss or maintain physical activity. [17] In 2020, there are many causes for the fact that the treatment of patients is not usually consistent with evidence-based guidelines. The most crucial factor of the physician's non-adherence are not providing adequate treatment.…”
Section: Physician Contributing Factors Of Adherence To Evidencebased Guidelines In Diabetes Mellitus Typementioning
confidence: 99%